(untitled) (Research, Society and Development, 2026)
This scoping review analyzes the interdisciplinary work of psychologists and psychiatrists in palliative care (PC) provided in primary health care (PHC). The research is justified by the need to understand how these professionals contribute to expanded care, given the existing gaps in the early identification of eligible patients, interprofessional communication, and the definition of specific competencies for interdisciplinary practice. The objective is to analyze and characterize the interdisciplinary work of psychologists and psychiatrists in PC in PHC, seeking to identify their independent, dependent, and interdependent actions and the skills/competencies required. Thus, the guiding question is formulated: “How is the performance of psychiatrists and psychologists in palliative care in Primary Health Care characterized?” The protocol was developed according to PRISMA-ScR and the Joanna Briggs Institute Manual for Evidence Synthesis (2024), using the PCC model to guide the eligibility criteria. The systematic search was conducted in the MEDLINE, LILACS, Plataforma Web of Science e Scopus databases, with no time limit and including complete studies in Portuguese, English, or Spanish. The last search took place on January 29, 2026. The selection will be conducted by two independent reviewers, with support from Rayyan QCRI, following the PRISMA flowchart. A total of 1447 studies were identified. Preliminary findings indicate that the integration of psychology and psychiatry favors the acceptance, symptom management, and quality of life of patients and family members, supporting the development of techno-assistance tools for PHC. Funding: PIBITI/PROPESQ–UFCAT (2025–2026).